The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1007/s12034-007-0034-5
|View full text |Cite
|
Sign up to set email alerts
|

Generation and characterization of nano aluminium powder obtained through wire explosion process

Abstract: In the present study, nano aluminium particles were produced by wire explosion process (WEP) in nitrogen, argon and helium atmospheres. Thus produced nano particles were characterized through certain physico-chemical diagnostic studies using wide angle X-ray diffraction (WAXD) and by energy dispersive analysis by X-rays (EDAX). The size and shape of the powder were analysed by using transmission electron microscopic (TEM) studies. The particle size distribution studies were performed by adopting log-normal pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…Ivanov et al [3] reported the production of particles of a smaller size, in the 30-50 nm range, by a similar technique. Similarly, Sarathi et al [4,5] and Sindhu et al [6] also reported the production and process control of nano-aluminium powders in combinations of inert media to obtain particles with the peak size in the 20-55 nm range at our laboratory.…”
Section: Introductionmentioning
confidence: 60%
“…Ivanov et al [3] reported the production of particles of a smaller size, in the 30-50 nm range, by a similar technique. Similarly, Sarathi et al [4,5] and Sindhu et al [6] also reported the production and process control of nano-aluminium powders in combinations of inert media to obtain particles with the peak size in the 20-55 nm range at our laboratory.…”
Section: Introductionmentioning
confidence: 60%
“…The aluminum nanopowder (ANP) sample was prepared at the High Voltage Research Institute of the Tomsk Polytechnic University by the method of electric explosion of wires [18,5] vation in argon-air mixture the sample was kept in closed flasks in ambient conditions. Characterization of ANP was carried out by physical and physico-chemical methods including scanning electron microscopy (Hitachi S-4800 equipped with EDX-analyzer), high resolution electron microscopy (JEOL JEM-3010), Xray diffraction (Shimadzu XRD 6000, Cu Ka -radiation), infrared spectroscopy (FTIR Nicolet-5700), particle size distribution was determined by means of Nanosizer ZS (Malvern Instruments) in ethyleneglycol medium at 25 8C.…”
Section: Methodsmentioning
confidence: 99%
“…Aluminum nanoparticles are the object of intense interest for use as a component in propellants [1,2] or in composite materials [3], their application is prospective in hydrogen power engineering [4]; other papers deal, e.g., with their physico-chemical properties [5,6], with their biological applications [7,8] or with their undesirable environmental effects [9]. High chemical activity of Al nanoparticles is caused by their small size and by their metastable structure [10].…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between size of the particle generated in the explosion process and the type of inert gas/pressure was analysed. It is realized that energy deposited to the conductor and duration of current flow have major impact on particles produced by this process 39 . In 2012, an experimental device based on the electrical explosion of metallic wires for the nanopowders production and collection was designed and built.…”
Section: Exploding Wirementioning
confidence: 99%